Penerapan Media Smart Box dan Komik Digital untuk Meningkatkan Keterampilan Menyusun Teks Tanggapan Fiksi dan Nonfiksi Siswa Kelas VII SMP N 1 Kembaran Banyumas - Mulatsari, Annisa Harum (Ruang Kata, 2025)
This study aims to improve the response text writing skills of grade VII students at SMPN 1 Kembaran Banyumas through the application of Smart Box and digital comic media. The method used is Classroom Action Research (CAR) with two cycles including planning, implementation, observation, and reflection. Data were collected through writing skill tests, student activity observation sheets, and student response questionnaires. The results showed a significant increase in students' ability to compose response texts, with the average score increasing from 73 in the first cycle to 80 in the second cycle, and the percentage of students achieving the Minimum Mastery Criteria (KKM) increasing from 60% to 90%. Smart Box and digital comics effectively increased students’ motivation, comprehension of reading content, and ability to write critical and structured responses.